Fishermen’s Behavior of Multi Ethnic Community in Adapting Climate Change in Small Island - Ihsannudin, Dwi Ratna Hidayati, Aminah H.M Ariyania, Subejo, Suadi (International Journal of Agricultural Sciences, 2017)
In a development perspective, small islands have limited economic access and opportunities, especially related to the economics of scale. Furthermore, the common problem such as climate change impact requires appropriate behavior of local inhabitant in order to survive in gaining to the economic access. Multi-ethnic society has different socio-cultural background that implies special characteristics and strategies to overcome climate change impacts. This study was conducted in Masalembu Island which consist of Madurese, Mandar, Bugis and Javanese ethnic. The aims of this study are to describe negative impact of climate change to the fisherman and to describe fisherman’s behavior for adapting climate changes. Theanalysis method is mixed method between the descriptive quantitative and qualitative analysis. The results show climate change causes fluctuating fish production, extending fishing ground to be more off-shore, uncertainty schedule for fishing and invasion from outer fisherman. Meanwhile, fishermen's behavior in overcoming the impacts of climate change consist of active response by Group of Fishermen, apply autonomous adaptation and apply adaptation behavior technologically, sociologically and regulatory. Based on these results, it is necessary to improve planned adaptation trough aquaculture, applying modern but friendlytechnology fishing gear and enhancing participation as well as cooperation among fisherman without ethnic consideration.